Machinery retrofiting for industry 4.0 - Torres, Pedro (2021)
“This is a post-peer-review, pre-copyedit version of an article published in Lecture Notes in Mechanical Engineering. The final authenticated version is available online at: https://doi.org/10.1007/978-3-030-79168-1_20".